Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1530/eje.0.1510193
|View full text |Cite
|
Sign up to set email alerts
|

A promoter polymorphism of the CYP27B1 gene is associated with Addison's disease, Hashimoto's thyroiditis, Graves' disease and type 1 diabetes mellitus in Germans

Abstract: The CYP27B1 promoter (-1260) C/A polymorphism appears to be associated with endocrine autoimmune diseases but the CYP27B1 intron 6 (+2838) C/T polymorphism appears to be associated only with Hashimoto's thyroiditis. These results imply a regulatory difference of the CYP27B1 hydroxylase to predispose to endocrine autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 26 publications
1
62
1
3
Order By: Relevance
“…In contrast, two recent small studies have shown association of CYP27B1 promoter alleles within trio families with Type 1 diabetes (Lopez et al 2004a) and in a case-control design in cohorts of patients with Addison's disease, GD, Hashimoto's thyroiditis and Type 1 diabetes from the German population (Lopez et al 2004b). Replication of these findings in an independent patient cohort would be an important step forward in confirming these potentially exciting findings.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, two recent small studies have shown association of CYP27B1 promoter alleles within trio families with Type 1 diabetes (Lopez et al 2004a) and in a case-control design in cohorts of patients with Addison's disease, GD, Hashimoto's thyroiditis and Type 1 diabetes from the German population (Lopez et al 2004b). Replication of these findings in an independent patient cohort would be an important step forward in confirming these potentially exciting findings.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, polymorphisms of the CYP27B1 hydroxylase gene catalyzing the conversion of 25 hydroxyvitamin D 3 (25(OH)D) to its active form were also associated with HT (69). Vitamin D levels were associated with VDR and vitamin D level-related genetic variants (70,71).…”
Section: The Role Of Vitamin D Deficiencymentioning
confidence: 99%
“…Diverse genetic variations predispose to autoimmune AD (20,21,22). Most of them are susceptibility factors for autoimmunity in general.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%